Kajian Potensi Komoditi Perkebunan sebagai Bahan Baku Biodiesel untuk Pengembangan Energi Terbarukan: Study of the Potential of Plantation Commodities as Biodiesel Raw Materials for Renewable Energy Development - Tambarta, Emmia; Sinta, Irada; Nasution, Wahyu Isnanda; Safitri , Sekar; Arnas, Eva (Universitas Medan Area, 2025)
Research on biodiesel sources from plantation crops such as jatropha, coconut, oil palm, and candlenut has been ongoing in Indonesia since the 1990s. However, many of these studies have been conducted in isolation. Utilizing the PICO framework to analyze diverse studies, researchers identified 13 relevant articles: seven focused on oil palm as a renewable energy source, four on candlenut, and two on jatropha. This distribution indicates that biodiesel research in Indonesia predominantly centers on oil palm, positioning it as the primary focus for renewable energy development. Nevertheless, the high costs and lengthy processes associated with collecting oil palm waste present significant challenges for its practical use in biodiesel production. Interviews with stakeholders from PAG Arun in Lhokseumawe suggest that jatropha may serve as a more viable biodiesel feedstock in Aceh due to its adaptability, ease of cultivation, and lower production costs. Furthermore, as jatropha remains largely underutilized in the region, it offers a promising and more cost-effective alternative for sustainable biodiesel production compared to other crops.